Bronchopneumonia and Multiorgan Dysfunction in a 10-month-old Infant with Down Syndrome - Dwi Wulandari; Yusian Eri Fitria (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2026)
Background: Common chromosomal disorder like Down Syndrome (DS) are linked to a high rate of congenital abnormalities, especially hypothyroidism and congenital heart disease (CHD). Presentation Case: This case report presents a 10-month-old female with DS who was brought to the emergency department with respiratory distress, poor weight gain, and delayed development. Physical examination revealed characteristic dysmorphic features, hypotonia, and a systolic murmur. Investigations showed elevated TSH and FT4, consistent with congenital hypothyroidism, while echocardiography confirmed the presence of ASD. Discussion: This case illustrates the multisystem involvement commonly observed in Down syndrome, including congenital hypothyroidism and atrial septal defect both major contributors to morbidity and mortality. The co occurrence of recurrent respiratory infections, heart disease, and endocrine dysfunction underscores the need for early screening, multidisciplinary management, and comprehensive care to improve outcomes in children with Down syndrome.Conclusion: Early detection of CHD and hypothyroidism in children with Down syndrome is essential to prevent complications and support optimal growth and development through timely, multidisciplinary intervention.